The impact of private school teachers' views of school climate on their perceptions of job security - Turhan, Esra; í‡apanoÄŸlu, Ceren (Jurnal Cakrawala Pendidikan, 2025)
The current study examined the effects of private school teachers' views about school climate on their job security perceptions. The study was designed using the correlational model, which is one of the quantitative research methods. The study's sample group consists of 294 teachers working in private secondary schools located in the í‡ankaya district of Ankara. Data were collected through the "Job Security Perception Scale" and the "Organizational Climate Scale" and analyzed by using descriptive statistics, the Pearson product-moment correlation coefficient model, and multivariate linear regression analysis technique. The results obtained from the research indicate that private school teachers' job security perceptions are slightly below the moderate level, while their views on the dimensions of school climate are generally at the moderate level. There are statistically significant relationships between private school teachers' job security perceptions and their views on the school climate. According to the findings concerning the final sub-question of the research, the views of private school teachers on the school climate predict approximately 55% (R2=0.545) of their job security perceptions. When the dimensions of the school climate are examined separately, it is observed that a significant portion of this effect is attributed to supportive principal behavior, which positively influences job security perceptions. Based on the results obtained from the research, it is recommended that measures be taken to inspect the working conditions of private school teachers and enhance the administrative support provided to them.